New species of Rosa L. and Veronica L. for the territory of National Nature Park Homilshanski Lisy - Timoshenkova, V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The results of the research of the flora of National Nature Park Homilshanski Lisy are presented. Two plants species new for the flora of Homilshanski Lisy and the flora of Kharkiv Region: Rosa rubiginosa L. (Rosaceae) and Veronica dillenii Crantz (Scrophulariaceae) were recorded on the Siversky Donets River sand terrace. R. rubiginosa is Europuen and Small-Asian species, which was recorded earlier at Left Bank Region of Dnipro River in Dnipropetrovsk Region and Sumy Region. At the National Nature Park R. rubiginosa grows as a part of natural plant communities in typical for this species ecotopes. The author assumes that the discovered places are within its natural range. The obtained data give possibility to enlarge R. rubiginosa range farther to East and to add Kharkiv Region. V. dillenii is widely distributed in Ukraine species, but in Kharkiv Region it was recorded for the first time. The new place of growth of Dactylorhiza incarnatа (Orchidaceae) included in the Red Book of Ukraine was found on the flood-land of Siversky Donets River within the economic zone of the National Nature Park. This information gives possibility to correct farming in order to maintain favorable conditions for the local population living.